A general approach to nitrile- and sulfonyl fluoride-substituted cyclopropanes. Issue 27 (22nd June 2021) - Zhang, Zai-Wei; Rakesh, K. P.; Liu, Jing; Qin, Hua-Li; Tang, Haolin
Abstract : A method for the synthesis of nitrile- and sulfonyl fluoride-substituted cyclopropanes through cyclization of 2-arylethensulfonyl fluorides with sulfur salt, is developed. Abstract : Both cis and trans relative configurations of functionalized cyano cyclopropane bearing sulfonyl fluoride moiety were accessed by Corey–Chaykovsky cyclopropanation reactions. This protocol used mild conditions, and obtained good yields with excellent functional group compatibility. Further application of this class of compounds in SuFEx reactions and cyano reductions were also successfully achieved in good yields.